2022
DOI: 10.1177/11795549221134831
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Biomarkers in Liquid Biopsy for Early Detection of Breast Cancer: A Systematic Review

Abstract: Background: Breast cancer (BC) is the most common neoplasm in women worldwide. Liquid biopsy (LB) is a non-invasive diagnostic technique that allows the analysis of biomarkers in different body fluids, particularly in peripheral blood and also in urine, saliva, nipple discharge, volatile respiratory fluids, nasal secretions, breast milk, and tears. The objective was to analyze the available evidence related to the use of biomarkers obtained by LB for the early diagnosis of BC. Methods: Articles related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 304 publications
0
3
0
2
Order By: Relevance
“…La BL ha permitido la identificación de diversos biomarcadores que son de gran utilidad clínica en el diagnóstico y tratamiento del cáncer de mama (10,11). Entre los biomarcadores más relevantes se encuentran:…”
Section: Biomarcadores Identificados Y Su Utilidad Clínicaunclassified
See 1 more Smart Citation
“…La BL ha permitido la identificación de diversos biomarcadores que son de gran utilidad clínica en el diagnóstico y tratamiento del cáncer de mama (10,11). Entre los biomarcadores más relevantes se encuentran:…”
Section: Biomarcadores Identificados Y Su Utilidad Clínicaunclassified
“…La BL ha revolucionado el diagnóstico del CM al permitir la detección temprana de la enfermedad y la estratificación de pacientes en función de biomarcadores específicos (11,22). Al analizar biomarcadores como el ADN tumoral circulante (ctDNA) y el ARN mensajero circulante (ctRNA), la BL puede identificar la presencia de células tumorales en etapas iniciales, incluso antes de que aparezcan síntomas clínicos (4,11,12,14).…”
Section: Contribución Al Diagnóstico Precoz Y Estratificación De Paci...unclassified
“…Liquid biopsy has been proven in recent years as an effective tool for non-invasive diagnosis and followup for several pathologies in the wide context of personalized medicine [1][2][3]. Sources of samples for liquid biopsy are almost all body fluids, such as plasma, urine, and saliva, which contain several components considered to be biomarkers of the physiopathological state of an individual [4,5]. The accessibility of these samples and the recent development of suitable technologies has pushed liquid biopsy out of traditional laboratories toward point-of-care (POC) tests.…”
Section: Introductionmentioning
confidence: 99%
“…They are found in many different cell types and tissues and have been shown to play a role in a wide range of biological processes, including cell growth and proliferation, differentiation, and apoptosis. Recent studies have shown that miRNAs can also be found in body uids, such as blood and urine (4), where they can be easily isolated and quanti ed and can act as biomarkers for various diseases, including cancer (5,6).…”
Section: Introductionmentioning
confidence: 99%